(untitled) (Philosophy and Progress, 2021)
This article examines Basil Anthony Moreau’s philosophy of education, and particularly his idea of Christian education. Moreau is the founder of the Congregation of Holy Cross that has been working on education and evangelization since 1853 in different countries of the world including Bangladesh. His philosophy of education plays a significant role in guiding and running Holy Cross educational institutions across the globe. Moreau’s educational philosophy envisioned three aims for all students in Holy Cross education: to develop the necessary skills and knowledge to function in the world and the hereafter; to nurture an appreciation for individual responsibility and social connectedness to advance social justice issues; to stimulate those critical dispositions of mind and heart essential to the sustenance of a peaceful society. He had the vision to educate both the hearts and minds of Christian students to grow in Christ’s love and make the world a better place. His views on education also have inspired Holy Cross education the pursuit of academic excellence within a family’s atmosphere that binds the student, faculty, staff, and alumni. Although Holy Cross educators did not implement the specific teaching methods of Moreau in all of their institutions, Moreau’s views laid the foundation of educational philosophy in Holy Cross education. Philosophy and Progress, Vol#63-64-; No#1-2; Jan-Dec 2018 P 65-80